2020
DOI: 10.1186/s12913-020-05375-3
|View full text |Cite
|
Sign up to set email alerts
|

Using intervention mapping to develop an occupational advice intervention to aid return to work following hip and knee replacement in the United Kingdom

Abstract: Background: There are increasing numbers of total hip replacements (THR) and total knee replacements (TKR) being performed in patients of working age. Providing patients undergoing TKR and THR with return to work advice might facilitate return to work. The aim of this paper is to report on the process used to systematically develop an occupational advice intervention to be delivered in hospital for those undergoing arthroplasty. Methods: The six-step Intervention Mapping (IM) approach to development, implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…To our knowledge, in comparison to other IM studies for RTW interventions [ 78 , 79 ] this is the first time IM approach that has been applied for a RTW intervention to be used directly by employers, managers and the workers themselves, without the involvement of healthcare professionals (HCP), RTW coordinators or providers (the provision of three coaching sessions in this intervention is provided to facilitate intervention engagement). This is important given that traditional RTW support, mostly offered by HCP or providers, tends to be inconsistent and does not always reach people with poor mental wellbeing [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, in comparison to other IM studies for RTW interventions [ 78 , 79 ] this is the first time IM approach that has been applied for a RTW intervention to be used directly by employers, managers and the workers themselves, without the involvement of healthcare professionals (HCP), RTW coordinators or providers (the provision of three coaching sessions in this intervention is provided to facilitate intervention engagement). This is important given that traditional RTW support, mostly offered by HCP or providers, tends to be inconsistent and does not always reach people with poor mental wellbeing [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in line with the hierarchy of risk management it is more ethical to start with adjusting the work to the patient’s needs, especially if the work is knee-straining. Recent studies have shown that interventions supporting RTW in arthroplasty patients based on knowledge for safe recovery, also regarding work-related activities, and sustainable RTW are being developed [ 11 , 29 , 30 ]. Managing too high patient expectations has also been suggested in TKA patients for better patient-reported outcome as well as RTW [ 12 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the orthopedic surgeon refers patients with hindering factors for RTW to their OMS, preferably before surgery, this might enhance a timely RTW if the OMS is able to act accordingly. RTW advise probably should also be individualized and needs involvement of the employer, as has been found in an intervention mapping approach to develop a clinical occupational advice intervention for knee arthroplasty patients [ 11 , 38 ]. M/-eHealth could be another promising add-on intervention, since it can provide personalized and frequent advice for TKA patients regarding timely performance of activities based on for instance activity trackers, self-reported recovery and algorithms [ 29 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation